Assessing the impact of systemic conditions on periodontal health in Malaysian population: a retrospective study - Sohaib Arshad; Raja Azman Awang; Normastura Abd Rahman; Akram Hassan; Wan Muhamad Amir W. Ahmad; Roshan Noor Mohamed; Sakeenabi Basha; Mohmed Isaqali Karobari (BMC, 2024)
Abstract Background Periodontal diseases, including gingivitis and periodontitis, are among the most prevalent oral health issues globally. They compromise the supportive structures of teeth and are influenced by both local and systemic factors. This study aimed to systematically assess the impact of systemic conditions on periodontal health in Malaysian population, addressing the gap in understanding these factors as potential risk factors. Methods A retrospective, non-interventional study was conducted using medical records from Hospital Universiti Sains Malaysia, Kelantan, from September 2019 to December 2022. The study included patients with periodontitis and systemic conditions. Data were analyzed using descriptive statistics, chi-squared tests, Fisher's exact tests, Mann-Whitney U tests, Kruskal-Wallis tests, Spearman's correlation, and logistic regression. Results Out of 600 records, 274 patients were included. The cohort was 51.8% male, with a median age of 51 years. Malays accounted for 92.3% of the sample. Hypertension and diabetes mellitus were the most common comorbid conditions. Severe periodontitis was significantly associated with age (45-64 years, p = 0.018) and Malay ethnicity (p = 0.011). Logistic regression revealed that age and ethnicity were significant predictors of periodontitis severity, with Malays being 12.5 times more likely to develop severe periodontitis. Conclusion Systemic conditions significantly influence periodontitis development and progression. Age and ethnicity are crucial predictors of periodontitis severity in the Malaysian population. Comprehensive risk assessment tools are necessary to incorporate a broader spectrum of risk factors for better management and prevention.